Analysis of scientific production on schizophrenia - da Silva, Juliana Lidiane Rêgo; Santos, Livia Maria de Melo; de Lima, Uirassú Tumpinambá Silva; dos Santos, Tâmyssa Simões; Santos, Karen da Silva; de Barros, Pétalla Morganna Figueiredo Pessoa (Journal of Health Care, 2016)
Introduction: Schizophrenia, object of this review, is a chronic degenerative mental disease. It occupies the top position of the mental illness list, being considered the most serious mental disorder, with significant repercussions on public health. Schizophrenia is known as a deteriorating phenomenon, which causes damages on the life of the affected person and his family. Goals: To analyze the scientific literature about schizophrenia, in the period between 1983 and 2015, published at REBEn. Methods: This is an integrative literature review. The literature research was made in the journal REBEn, which can be found on the following databases: Lilacs, Nursing Index, CINAHL and Scielo. The research included original articles with full text available in electronic support. The descriptors used were: schizophrenia, mental suffering and nursing. Seven scientific articles were selected and analyzed. Results: In 2005 and 2012, the higher number of publications could be found. Regarding the authorship of the articles, most had the participation of masters and doctors. Most of the researched production was concentrated in the Southeast Region, with unanimous qualitative approach. Hospitals were the biggest scenario of this research. Conclusion: There are few studies published in Nursing about schizophrenia, as evidenced by the decreasing of production about it for 32 years of publication of REBEn. The scientific productions proved to be important to change behaviors on nursing practice, however, there is a need for more studies on this subject.
Keywords: schizophrenia; psychological distress; nursing